2017
DOI: 10.1371/journal.pone.0167764
|View full text |Cite
|
Sign up to set email alerts
|

Emerging New Crop Pests: Ecological Modelling and Analysis of the South American Potato Psyllid Russelliana solanicola (Hemiptera: Psylloidea) and Its Wild Relatives

Abstract: Food security is threatened by newly emerging pests with increased invasive potential accelerated through globalization. The Neotropical jumping plant louse Russelliana solanicola Tuthill is currently a localized potato pest and probable vector of plant pathogens. It is an unusually polyphagous species and is widely distributed in and along the Andes. To date, introductions have been detected in eastern Argentina, southern Brazil and Uruguay. Species distribution models (SDMs) and trait comparisons based on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Our results further disclosed that, despite the highest infestation rates of all insects, the peak development of Lacetta and SH-5 proved that these varieties are most resistant/tolerant, while the minimum growth of Hannat white with the highest infestation rates for Aphid (14.43), Leafhopper (17.72), Thrips (7.22) and Whitefly (12.97) found this range to be more prone to different insects/pests. These findings are consistent with Syfert et al [47], who found that these species were more likely to be impacted by insects.…”
Section: Whiteflysupporting
confidence: 92%
“…Our results further disclosed that, despite the highest infestation rates of all insects, the peak development of Lacetta and SH-5 proved that these varieties are most resistant/tolerant, while the minimum growth of Hannat white with the highest infestation rates for Aphid (14.43), Leafhopper (17.72), Thrips (7.22) and Whitefly (12.97) found this range to be more prone to different insects/pests. These findings are consistent with Syfert et al [47], who found that these species were more likely to be impacted by insects.…”
Section: Whiteflysupporting
confidence: 92%
“…In a number of studies, researchers have used similar approaches to explore effects of global change on antagonistic interactions between plants and their associates by extracting data on herbivores, herbivory, and plant pathogens (Malmstrom et al , 2007; Lees et al , 2011; Youngsteadt et al , 2015; Syfert et al ., 2017). However, methods remain relatively underdeveloped.…”
Section: Gaps In the Application Of Herbarium Datamentioning
confidence: 99%
“…[3–7]). This, coupled with climate change and globalization, has raised the risk of these species reaching areas and countries that would have not been inhabited a few decades ago [810]. As a consequence, psyllid taxonomy and systematics is of primary importance, not only for a better understanding of worldwide biodiversity, but also in order to recognise new or invasive species essential for international biosecurity and plant protection.…”
Section: Introductionmentioning
confidence: 99%